Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae) - Budak Mahi̇r; Blank, Stephan M.; Başibüyük, Hasan H. (Zootaxa, 2017)
Trachelus stipa is described from Central Anatolia, Turkey. It is morphologically close to T. flavicornis and T. troglodyta regarding the structure of the preapical sterna of the male. It is unique among Trachelus species regarding the shape of the claw of the posterior leg, the size of the denticles of the ovipositor and the short valvula 3 of the ovipositor sheath in the female, and the distally notched hypopygium in the male. The genetic distance found in two mitochondrial (COI and cyt b) and one nuclear (EF-1α) gene regions support the recognition of this species and its placement within Trachelus, although the shape of the ovipositor sheath disagrees with this concept. Stipa holosericea, the host of T. stipa according to field observations, represents the first record of a feather grass as the host of a sawfly species.